Subsistence Ethics of Smallholder Coffee Grower: Understanding the Dynamics of Agroforestry Development in the Upland of South Sumatra - Martin, Edwin; Suharjito, Didik; Darusman, Dudung (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTThe importance of agroforestry for smallholder farmers has been the discourse and policies of many parties worldwide. However, agroforestry development through land rehabilitation, reforestation and community forests for traditional coffee growers in the uplands has not shown success yet. In fact, some of the innovations that come from the outside can be received by farmers. The study aims to describe the innovation adoption experienced by traditional coffee farmers in Semende, with a focus on the development of agroforestry program. The research was conducted with descriptive phenomenological approach. The research findings indicate that the cautious attitude of farmers in accepting the innovation brought by the government congruent with the concept of Scott’s subsistence ethics, but in a different context. For coffee farmers, subsistence ethics is a perspective on collateral sufficiency cash income to meet the needs of food and other necessities of life, so it does not depend on other people and socially can follow the life of the village, not only a security for could still life. Traditional coffee farmers in Semende just planted a few trees in the garden to avoid risks that could reduce the guarantee to live independently. We suggest that the policy of land rehabilitation, reforestation and agroforestry in coffee plantations plateau (upstream) as in Semende designed based on the principles that strengthen the self-reliance of farmers.Keywords: agroforestry, land rehabilitation, coffee farmers, subsistence ethicsABSTRAKNilai penting agroforestri bagi petani kecil telah menjadi wacana dan kebijakan banyak pihak di seluruh dunia. Namun, pengembangan agroforestri melalui program rehabilitasi lahan, penghijauan dan hutan rakyat bagi petani kopi tradisional di dataran tinggi belum menunjukkan keberhasilan. Pada kenyataannya, beberapa inovasi yang datang dari luar dapat diterima petani. Penelitian bertujuan untuk mendeskripsikan adopsi inovasi yang dialami petani kopi tradisional di Semende, dengan fokus terhadap program pengembangan agroforestri. Penelitian dilaksanakan dengan pendekatan fenomenologis deskriptif. Temuan penelitian menunjukkan bahwa sikap hati-hati petani dalam menerima inovasi yang dibawa oleh pemerintah sebangun dengan konsep Scott tentang etika subsistensi, namun dalam konteks yang berbeda. Bagi petani kopi, etika subsistensi adalah perspektif tentang jaminan kecukupan pendapatan tunai untuk memenuhi kebutuhan pangan dan kebutuhan hidup lainnya, sehingga tidak tergantung kepada orang lain dan secara sosial dapat mengikuti kehidupan desa, bukan sekedar jaminan untuk tetap dapat hidup. Petani kopi tradisional di Semende hanya menanam sedikit pohon dalam kebun untuk menghindari resiko yang dapat mengurangi jaminan hidup mandiri. Kami menyarankan agar kebijakan rehabilitasi lahan, penghijauan dan agroforestri di kebun kopi dataran tinggi (hulu DAS) seperti di Semende dirancang berdasarkan prinsip yang menguatkan keswadayaan petani.Kata kunci : agroforestri, rehabilitasi lahan, petani kopi, etika subsistensi